ChemInform Abstract: An Efficient, Thermally Stable Cerium‐Based Silicate Phosphor for Solid State White Lighting. Issue 38 (30th August 2013) - Brgoch, Jakoah; Borg, Christopher K. H.; Denault, Kristin A.; Mikhailovsky, Alexander; DenBaars, Steven P.; Seshadri, Ram
Abstract Polycrystalline samples of Ba9 (Y1‐xCex)2Si6O24 (x = 0—0.12 in steps of 0.02) and Ba9 (Y1‐yScy) 1.94Ce0.06Si6O24 (y = 0.05—0.25 in steps of 0.05) are prepared by solid state reaction of stoichiometric mixtures of BaCO3, Y2O3, Sc2O3, SiO2, and CeO2 (5% H2/N2 atmosphere, 1350 °C, 4 h).